IMPLICATIONS OF TAX AVOIDANCE AND EVASION ON TAX COLLECTION IN THE PERUVIAN AMAZON - Huaytan Tucto, Luis (2024)
The Peruvian tax system has implemented a series of benefits, exemptions, and exclusions with the aim of alleviating the tax burden and stimulating investment. However, the impact of these incentives on tax collection and economic development requires detailed evaluation. This study focuses on the Amazon Region, an area with characteristics such as high economic informality, tax evasion, and avoidance, which affect both tax collection and socioeconomic development. Law No. 27037, created to encourage investment in the Amazon, has shown mixed results and has led to a reevaluation of its effectiveness and the possibility of its elimination.The research adopted a qualitative approach combined with a descriptive analysis of public data. A non-experimental correlational design was used to observe the relationship between tax evasion and avoidance variables without directly intervening in the study environment. The methodology included the collection and analysis of tax data from the region, as well as a review of previous studies and relevant legislative documents. Preliminary findings reveal that tax incentives in the Amazon have not achieved the expected results. The tax evasion rate in some areas of the region reaches up to 80%, while 2018 data indicate a general evasion rate of 19%. These figures suggest a significant disconnect between the granted fiscal benefits and the actual impact on tax collection. The experience in San Martín, where certain tax benefits were removed, shows an improvement in collection and could offer a replicable model for other regions.High tax evasion and the prevalence of the informal economy severely limit the government’s ability to raise funds and finance essential public services. Despite the tax incentives, poverty in the region has increased, questioning the effectiveness of the implemented policies. It is observed that economic informality and the lack of effective control mechanisms significantly contribute to the problems of tax evasion.The research suggests that a thorough review of the tax policies applicable to the Amazon Region is required. It is essential to strengthen fiscal control mechanisms and improve oversight of tax incentives to enhance compliance. Additionally, a review and adjustment of tax benefits are recommended to ensure they are effective in promoting economic development and reducing poverty. Strengthening the institutions responsible for oversight and promoting tax education are crucial steps to address the challenges of tax evasion and avoidance in the region and to foster more equitable and sustainable economic development. KEYWORDS: Avoidance, tax evasion, tax collection.